Pengaruh Faktor-Faktor Total Quality Management (TQM) Terhadap Kinerja Karyawan (Studi Pada Kantor Pelayanan Pajak Kabupaten Subang Jawa Barat) - Naufal, Rosyad Fadhil; Sudaryanto, Budi (Faculty of Economics and Business Diponegoro University, 2019)
This study aims to determine the effect of Total Quality Management of employee performance at Tax Office in Subang West Java through four TQM factors namely Commitment, Employee Involvement and Empowerment, Continuous Improvement, and Teamwork. The data analysis method used in this study is Multiple Regression Analysis is used to determine the effect of change a variable to another variable. The population in the study were all employees of Tax Office Subang Jawa Barat. Sample of 76 people with using saturated sampling techniques. The results showed that the model was feasible based on the classical assumption. Technique of multiple linear regression analysis indicating that all independent variables have a significant influence on the dependent variable with a confidence level of 5 percent, except for the variable Employee Involvement and Empowerment, Continous Improvement that does not qualify as a variable that significantly influence the Employee’s Performance due to have a significance value above 5 percent.